KOMPETENSI KEPALA MADRASAH DALAM MENGELOLA KONFLIK ANTAR SANTRI DI MTS PONDOK PESANTREN ABNAUL AMIR KABUPATEN GOWA - Irma Fatimah; Yuspiani, Yuspiani; Wayong, Moh. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the phenomenon of student conflict in Islamic boarding school–based education, focusing on the role of the madrasah principal in managing such conflicts at MTs Pondok Pesantren Abnaul Amir, Gowa. High social interaction among students with diverse backgrounds often leads to disputes, disciplinary violations, and seniority issues that affect the educational climate. This research aims to analyze the principal’s competencies in handling student conflicts and the strategies applied to create a peaceful school environment. A descriptive qualitative approach was employed through participatory observation, in-depth semi-structured interviews, and documentation involving the principal, teachers, staff, and students. Data were analyzed using the interactive model of Miles and Huberman, and validity was ensured through triangulation and credibility techniques. The findings reveal that student conflicts were addressed not merely through punitive measures but through persuasive communication, mediation, musyawarah, and islah approaches. The principal’s managerial, social, and personal competencies played a crucial role in strengthening discipline, improving supervision, and fostering harmonious relationships among students. Conflict management practices in this madrasah demonstrate that conflicts can be transformed into constructive character-building processes when handled with appropriate leadership strategies rooted in Islamic educational values.